Ultrastructural analysis of fine needle aspirates from benign breast lesions. Issue 1 (January 1990) - Ferguson, D J; Wells, C A; Crucioli, V
Abstract : Thirty six fine needle aspirates from various types of benign breast lesions were examined by electron microscopy and correlated with their cytological appearances. In all cases the parenchyma consisted of clumps of cohesive cells with the ultrastructural features of epithelial cells. In many cases, particularly from fibroadenomas, the parenchyma consisted of single layers of polarised epithelial cells showing lumen formation. Similar arrays of apocrine epithelial cells were observed in 60% of fibrocystic lesions. The more solid clumps from hyperplastic lesions consisted of epithelial cells of variable shape and electron density with disorganised lumen formation. Irrespective of the type of lesion, the epithelial cells were not normally subtended by myoepithelial cells or basal lamina. The extraction process seems to result in a shearing between the epithelium and basal lamina with lysis of the myoepithelial cells. Most naked nuclei probably result from lysed myoepithelial cells.